Secondary implant stability in autologous one-stage internal and external sinus floor elevation using resonance frequency analysis – a three-month follow up - Katharina Schaffrath; Kristian Kniha; Mark Ooms; Philipp Winnand; Nils Vohl; Britta Lohn; Frank Hölzle; Ali Modabber (Clinical Oral Investigations, 2026)
Abstract Objectives The aim of this retrospective study was to evaluate implant stability using resonance frequency analysis (RFA) (Osstell ® W&H, Mettmann) for autologous one-stage sinus floor elevation with implantation and provide advice regarding the healing procedure and the timing of implant loading. Materials and methods After 3 months, 145 implants were evaluated for secondary implant stability using RFA. Of the evaluated implants, 72 were set in original bone (OB) in the upper posterior jaw, 21 were set in combination with a one-stage autologous external sinus floor elevation (EE), and 52 in combination with internal elevation (IE). Results Osseointegration was significantly higher in OB (94,4%) compared to EE (76,2%) and IE (80,8%). RFA values were best in the OB group (OB: 77,5 [8], EE: 75 [12], IE: 75 [8]; p = 0,030). Conclusion In general, autologous one-stage sinus floor elevation combined with implantation is a safe procedure, but we recommend a prolonged healing phase of at least four additional weeks for EE and IE procedures. Clinical relevance Although one-stage procedures require longer healing phases, treatment duration is still shorter than a two-stage procedure. Patients often prefer minimally invasive and short options because of anxiety and stress.